2022
DOI: 10.1111/jne.13182
|View full text |Cite
|
Sign up to set email alerts
|

ERK‐dependent induction of the immediate‐early gene Egr1 and the late gene Gpr50 contribute to two distinct phases of PACAP Gs‐GPCR signaling for neuritogenesis

Abstract: Gs‐coupled GPCR‐stimulated neuritogenesis in PC12 and NS‐1 ‐ cells depends on activation of the MAP kinase ERK. Here, we examine changes in ERK activation (phosphorylation), and the time course of ERK‐dependent gene induction, to seek transcriptional determinants for this process. Quenching of ERK activation by inhibition of MEK with U0126 at any time point for at least 24 h following addition of PACAP resulted in arrest of neurite formation. Changes in the transcriptome profile throughout this time period rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…These results indicate the importance for ERK and JAK2 signaling in mediating IEG upregulation after CEPO and IGF-1 treatment, while not implicating AKT signaling in this process. Previous research has noted the importance for ERK-mediated regulation of IEG expression [45,[47][48][49], which our results would corroborate. Since the IGF1R is a tyrosine kinase receptor, JAK2 signaling would be important for initiating its downstream signaling cascades, which could explain why inhibiting JAK2 causes such a robust decrease in gene expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results indicate the importance for ERK and JAK2 signaling in mediating IEG upregulation after CEPO and IGF-1 treatment, while not implicating AKT signaling in this process. Previous research has noted the importance for ERK-mediated regulation of IEG expression [45,[47][48][49], which our results would corroborate. Since the IGF1R is a tyrosine kinase receptor, JAK2 signaling would be important for initiating its downstream signaling cascades, which could explain why inhibiting JAK2 causes such a robust decrease in gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…IEG activation is thought to be regulated by multiple pathways including ERK, RhoA-actin, p38 MAPK, and PI3K [ 44 , 45 , 46 ]. To further implicate specific pathways in mediating the increased IEG expression seen after trophic factor treatment, three kinase inhibitors—GDC-0994, AZD-1480, and MK-2206—were used to inhibit either ERK, JAK2, or AKT, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been almost 30 years since this GPR50 was found to be expressed in chromosome X, yet the function of this receptor, which is found in parts of the brain (Hamouda et al, 2007) is not well known. In the neuronal-like rat cell line Neuroscreen-1 (NS-1), its expression has been associated with increased neurite outgrowth (Grünewald et al, 2009;Xu et al, 2022). Some sporadic studies suggest that GPR50 is involved in regulating energy homeostasis and fasting-induced torpor (Bechtold et al, 2012).…”
Section: Gpr50mentioning
confidence: 99%
“…Mutt Lecturer (RegPep22) Laura Bohn has also identified a pathway for mu receptor signaling through arrestin, bypassing G‐proteins altogether, and Andrew Emery and colleagues have shown that certain Gs‐coupled neuropeptide receptors may engage specific adenylyl cyclase isoforms in the cells, thus having actions that may be correspondingly restricted to soma, dendrites, axons or nerve terminals in neurons or elsewhere in other cell types. Wen Xu and colleagues have characterized a gene expression cascade leading to PACAP‐induced neuritogenesis in a PC12‐like neuroendocrine cell line 5 that proceeds through a cAMP➔ERK pathway enabled through the neuroendocrine‐specific guanine nucleotide exchange factor 2 and therefore a pathway unique to neurons and endocrine cells. Persistent extracellular signal regulated kinase signaling, dependent in turn on prolonged exposure to PACAP, results in induction of first a set of immediate‐early genes including Egr‐1 and then a set of late genes including Gpr50.…”
Section: Gpcr‐diversity and Convergence In Structure And Functionmentioning
confidence: 99%